+0  
 
0
25
1
avatar

What is the inverse of f(x)=(x+6)^2  for x≥–6 where function g is the inverse of function f?

 

 

g(x)=[√x]−6, x≥0

 

g(x)=[√x-6], x≥6

 

g(x)=[√x+6], x≥−6

 

g(x)=[√x] +6, x≥0

Guest Oct 24, 2018
 #1
avatar+90995 
+1

f(x)  = (x + 6)^2  for x  ≥ 6

 

For  f(x)......write y

 

y = ( x + 6)^2      take the square root of both sides

 

√y =  x + 6     subtract 6 from both sides and "swap"  x and y

 

√x  - 6   =   y      for y, write g(x)

 

So

 

g(x)  =  √x - 6   

 

Since  the first point on the original graph  is  (-6,0)

The first point on this graph  is  (0,-6)

So    x ≥ 0

 

 

cool cool cool

CPhill  Oct 24, 2018

25 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.